Secreted Frizzled Related Proteins in Cardiovascular and Metabolic Diseases - Guan, Hua; Zhang, Jin; Luan, Jing; Xu, Hao; Huang, Zhenghao; Yu, Qi; Gou, Xingchun; Xu, Lixian (Frontiers in Endocrinology, 2021)
Abnormal gene expression and secreted protein levels are accompanied by extensive pathological changes. Secreted frizzled related protein (SFRP) family members are antagonistic inhibitors of the Wnt signaling pathway, and they were recently found to be involved in the pathogenesis of a variety of metabolic diseases, which has led to extensive interest in SFRPs. Previous reports highlighted the importance of SFRPs in lipid metabolism, obesity, type 2 diabetes mellitus and cardiovascular diseases. In this review, we provide a detailed introduction of SFRPs, including their structural characteristics, receptors, inhibitors, signaling pathways and metabolic disease impacts. In addition to summarizing the pathologies and potential molecular mechanisms associated with SFRPs, this review further suggests the potential future use of SFRPs as disease biomarkers therapeutic targets.